Lewis, Mary - Nashville, Tenn. - Prostitution Charge
Special Collections -- Banner Archives -- Clippings -- Drawer 4129

Lewis, Mary - Nashville, Tenn. - School Principal
Special Collections -- Banner Archives -- Clippings -- Drawer 4129

Lewis, Mary Deloris - Nashville, Tenn. - Murder Charges
Special Collections -- Banner Archives -- Clippings -- Drawer 4129

Lewis, Mary - Columbia, TN. - Drug Charge
Special Collections -- Banner Archives -- Clippings -- Drawer 4129

Lewis, Mary Gabriel - Philadelphia - Charged with Harassment
Special Collections -- Banner Archives -- Clippings -- Drawer 4129

Lewis, Mary Ellen - Nashville, Tenn. - Commerce Union Bank
Special Collections -- Banner Archives -- Clippings -- Drawer 4129